Pengaruh Digital Fatigue terhadap Keputusan Pembelian pada Platform E-Commerce dengan Trust dan Emotional Escape Sebagai Variabel Mediasi pada Generasi Z di Kota Yogyakarta - Agus Mulyono; Danang Sunyoto (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the influence of digital fatigue on purchasing decisions on e-commerce platforms, with trust and emotional escape as mediating variables among Generation Z in Yogyakarta City. The phenomenon of high digital media usage intensity among Gen Z has led to digital fatigue, which has the potential to influence their consumption behavior. This study used a quantitative approach with a survey method of Generation Z respondents who actively shop through e-commerce. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that digital fatigue significantly influences purchasing decisions. Furthermore, trust and emotional escape are proven to act as mediating variables that strengthen and explain this relationship. Trust increases consumer confidence in making transactions, while emotional escape encourages purchasing behavior as a form of escape from digital fatigue . These findings provide theoretical implications for the development of digital consumer behavior literature and practical implications for e-commerce platform managers in designing marketing strategies that can manage digital fatigue and build consumer trust.